A New Hepatitis Virus Test with Microliter-scale Fingertip Blood Collection in Japan - Namba, Shihoko; Ikeda, Fusao; Takaguchi, Koichi; Shimomura, Yasuyuki; Yasunaka, Tetsuya; Okada, Hiroyuki (Acta medica Okayama, 2018)
We investigated whether a small amount of blood collected by fingertip blood sampling would be adequate in a mass examination for hepatitis virus infection in Japan. A cross-sectional survey was conducted at health fairs in Kasaoka City and Shodoshima Island, where participants took the hepatitis screening test. A total of 114 consecutive individuals who took the hepatitis screening test were enrolled. Twenty microliters of plasma was successfully obtained from all participants. Among the participants, two had positive results for HBs antigen and two were positive for anti-HCV; all four were > 60 years old and rarely visited the hospital. Thirty-three and 38 patients chronically infected with HBV and HCV, respectively, were examined for confirmatory assays at participating hospitals. All subjects with undetectable serum levels of HBs antigen and anti-HCV had undetectable levels of both markers in fingertip blood, and the levels in serum and fingertip blood were significantly correlated (p<0.01). The lower detection limit of HBs antigen was defined as 0.005 IU/ml, and the cut-off value of anti-HCV was 1.0 by using 10-μl fingertip blood samples. The fingertip blood sampling described herein may be adequate in mass examinations for hepatitis virus testing in Japan.